Crime of Incitement via Social Media: Rulings and Digital Evidence - Raghad Ali Alzahrani (International Journal of Law Research and Studies, 2025)
The study addressed the issue of criminal responsibility for incitement through social media in the Saudi legal system, considering it one of the modern crimes resulting from technological advancements and the widespread use of these platforms. The study examines the Saudi legal system as a model to clarify the legal aspects related to the crime of incitement through social media within the framework of Saudi legislation. Additionally, the study explores the concept of digital evidence in the crime of incitement via social media and its various types. The study concluded that social media plays a pivotal role in facilitating incitement activities due to its rapid spread and the lack of controls to prevent its misuse. It also highlighted that the Saudi legal system adopts clear legal provisions to criminalize incitement through these platforms, but challenges remain in implementing these provisions, especially in cases where the crime’s elements are incomplete. To address these challenges, the study recommended raising public awareness about the dangers of electronic incitement and its negative effects on individuals and society. It also emphasized the importance of enhancing the legal framework by developing advanced technologies to monitor cybercrimes. Additionally, the study called for imposing deterrent penalties to prevent the recurrence of such crimes while ensuring the protection of freedom of expression in a way that does not conflict with public order.